The influence of religiosity on health: the case of healthy/unhealthy habits - Rocío de Diego Cordero; Manuel Guerrero Rodríguez (Universidad de Alicante, 2019)
Introduction: In Spain, the religious pluralism can became a challenge to healthcare professionals in their role of providing coherent care and attention that respects the beliefs and values of usersen. Objective: The objective of this study is to know the influence of religiosity / spirituality on behavior patterns in relation to lifestyles: healthy and unhealthy habits. Methodology: Systematic literature review published between 2012-2017 and it searched in databases: SCOPUS, PUBMED, LILACS and WOS. Results: The 22 selected articles showed a direct relationship between the level of religiosity and the follow-up of healthy behaviors in general, as well as the protective character of the life styles in the appearance of diseases. Also, a low consumption of toxic substances was observed in people with greater religious participation. Conclusion: It can be affirmed that the affiliation to a religion does imply the realization of behavioral patterns that are usually beneficial to health. In addition, non-religious individuals with high levels of spirituality are also likely to engage in healthier behaviors than those with poorer levels.